إدارة الصراع كمدخل لتحسين عمليتي التخطيط والتنظيم في مدارس التعليم الابتدائي بمحافظة كفر الشيخ - سليمان، السعيد السعيد بدير; بيومي، شريهان عادل; رمضان، فريدة إبراهيم محمود (جامعة كفر الشيخ - كلية التربية, 2020)
يهدف البحث الحالي إلى التعرف على واقع عمليتي التخطيط والتنظيم بمدارس التعليم الابتدائي بمحافظة كفر الشيخ، واستخدمت الباحثة المنهج الوصفي، وتوصلت الدراسة إلى أن عمليتي التخطيط والتنظيم تعاني من كثير من الصعوبات في تحقيقها داخل المدارس والمؤسسات التربوية، وتوصل البحث إلى رصد بعض المعوقات التي كانت تحول دون تحقيق أدارة الصراع لمهامها وكان منها ضعف الرقابة الإدارية وطبيعة اتخاذ القرارات والتنظيمات غير الرسمية وعدم المساوة بين العاملين والصراع بين الإدارات المتشابهة وظيفيا ولهذا يهدف البحث إلى تحسين عمليتي التخطيط والتنظيم باستخدام مدخل إدارة الصراع ويتكون البحث من: • الإطار العام. • الإطار النظري. • عمليتي التخطيط والتنظيم بالمدارس. • نتائج البحث، ومقترحات تحسين عمليتي التخطيط والتنظيم باستخدام مدخل إدارة الصراع.
The current research aims to identify The reality of the Planning and Organizing Operations in Primary Education Schools in Kafr El Sheikh Governorate, and The researcher used The Descriptive Approach, And the study concluded that Planning and Organizational Operations suffers from Many Difficulties in achieving it within Schools and Educational Institutions, and the research reached to monitor some of the Obstacles that were transforming Without achieving Conflict Management for its tasks, including weak Administrative Control, The nature of Decision-making and Informal Organizations, and the lack of Equality between workers and Conflict between similarly functionally administered Departments, this is why the research aims to Improve the Planning and Organization Operations using The Conflict Management Approach. The research consists of: • General Framework. • Theoretical Framework. • Planning and Organization Operations in Schools. • Research findings and Proposals for Improving Planning and Organization Operations using The Conflict Management Approach.
Keywords: مدارس التعليم الابتدائي -- الإدارة المدرسية -- الأداء الإداري -- الصراع التنظيمي -- إدارة الصراع -- عملية التخطيط -- عملية التنظيم -- محافظة كفر الشيخ -- السعودية